Synapsin knockdown is associated with decreased neurite outgrowth, functional synaptogenesis impairment, and fast high-frequency neurotransmitter release - Brenes García, Oscar Gerardo (2015)
Synapsins (Syns) are an evolutionarily conserved family of synaptic vesicle-associated proteins related to fine tuning of synaptic transmission. Studies with mammals have partially clarified the different roles of Syns; however, the presence of different genes and isoforms and the development of compensatory mechanisms hinder accurate data interpretation. Here, we use a simple in vitromonosynaptic Helix neuron connection, reproducing an in vivo physiological connection as a reliable experimental model to investigate the effects of Syn knockdown. Cells overexpressing an antisense construct against Helix Syn showed a timedependent decrease of Syn immunostaining, confirming protein loss. At the morphological level, Syn-silenced cells showed a reduction in neurite linear outgrowth and branching and in the size and number of synaptic varicosities. Functionally, Syn-silenced cells presented a reduced ability to form synaptic connections; however, functional chemical synapses showed similar basal excitatory postsynaptic potentials and similar short-term plasticity paradigms. In addition, Syn-silenced cells presented faster neurotransmitter release and decreased postsynaptic response toward the end of long tetanic presynaptic stimulations, probably related to an impairment of the synaptic vesicle trafficking resulting from a different vesicle handling, with an increased readily releasable pool and a compromised reserve pool.